Intervensi Layanan Konseling untuk Mereduksi Kecemasan - Ririn Ayu Anjar Wani; Aisyah Ariesca Putri; Risma Anita Puriani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to analyze the effectiveness of counseling services in reducing anxiety in individuals through a literature review. Anxiety is a psychological condition characterized by excessive worry, emotional tension, and physical and cognitive impairments that can impact academic, social, and daily life activities. The study was conducted using a qualitative approach through data collection from various scientific articles, journals, and relevant library sources regarding counseling interventions to reduce anxiety. The research process included problem identification, literature collection, screening of relevant sources, data analysis, and synthesis of previous research findings. The study results indicate that various counseling approaches, such as Cognitive Behavioral Therapy (CBT), Acceptance Commitment Therapy (ACT), systematic desensitization techniques, cognitive restructuring, and relaxation techniques, have been proven effective in reducing individual anxiety levels. These interventions help individuals change negative thought patterns to more adaptive ones, improve their ability to regulate emotions, and reduce physiological responses to anxiety. Furthermore, a comfortable environment and structured counseling support also influence the success of the intervention. Thus, counseling services play a crucial role in helping individuals overcome anxiety and improve mental health and psychological well-being.